LOCAL COUNCIL DEPUTY ACTIVITY IN THE PUBLIC ADMINISTRATION SYSTEM: MECHANISMS FOR ENSURING EFFECTIVENESS (Coordinates of Public Administration, 2026)
The article examines the activity of a local council deputy as an important institutional component of the public administration system and one of the key determinants of effective local governance. It is substantiated that under conditions of deepening decentralisation processes, the functioning of local self-government during martial law, rapid digital transformation, and the increasing public demand for transparency and accountability of public authorities, the role of a local council deputy is acquiring a fundamentally new functional dimension. It has been established that contemporary deputy activity extends beyond a purely representative function and incorporates managerial, communicative, supervisory, coordination, and rule-making responsibilities aimed at ensuring the sustainable development of territorial communities and enhancing the performance of local self-government institutions. The study demonstrates that the effectiveness of local council deputy activity is determined not merely by the formal existence of a representative mandate but primarily by the capacity to represent the interests of the territorial community, participate in the formulation and implementation of local policy, exercise oversight over the implementation of managerial decisions, maintain systematic interaction with citizens and stakeholders, and adhere to the principles of integrity and ethical standards of public activity. It has been determined that the effectiveness of deputy activity directly affects the level of public trust in local authorities, the quality of managerial decision-making, and the overall effectiveness of local policy implementation. The article identifies the principal mechanisms for ensuring the effectiveness of local council deputy activity, including representative, rule-making, supervisory, communicative-consultative, information-analytical, ethical, digital, and partnership-coordination mechanisms. The necessity of their functioning as an integrated and interconnected system aimed at improving the quality of local governance, ensuring transparency of managerial processes, strengthening institutional accountability, and enhancing effective interaction between public authorities and territorial communities is substantiated.